Electronic Word of Mouth and Brand Image on Purchasing Decisions Through Perceived Value - Dhini Aprilia Putri; Brahma Wahyu Kurniawan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine how electronic word of mouth (e-WOM) and brand image influence consumer purchasing decisions for PT Naturindo Surya Niaga's herbal products, with perceived value as a mediating variable. The research method uses a quantitative approach with the principle of positivism, through an accidental sampling technique on 130 consumers of PT. Naturindo Surya Niaga. Data were collected through questionnaires and analyzed using Partial Least Square (PLS) using SmartPLS 3.0. The results show that e-WOM has a positive and significant effect on perceived value, but does not directly influence purchasing decisions. In contrast, brand image has a strong and significant influence on both perceived value and purchasing decisions directly. Perceived value is proven to act as an effective mediator in connecting e-WOM and brand image with purchasing decisions. These findings emphasize that herbal companies need to optimize digital communication strategies through authentic consumer reviews and brand image strengthening to increase value perception and encourage purchases amidst intense e-commerce competition.